2019
DOI: 10.2147/prbm.s206636
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association between transformational leadership and occupational burnout and the mediating effects of psychological empowerment in this relationship among CDC employees: a cross-sectional study</p>

Abstract: Purpose: Centers for Disease Control and Prevention (CDC) is playing a vital role in protecting public health and safety. However, few studies have researched on the occupational burnout of CDC employees in the world. Previous studies have reported that transformational leadership could improve the level of psychological empowerment and ameliorate burnout of the employees. In this study, we aimed to analyze the association between transformational leadership and burnout and to test the mediating rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 38 publications
2
36
0
2
Order By: Relevance
“…However, our survey results also indicated a lack of appreciation by the affected communities regarding the work performed by the public health workers [ 33 ]. Our data showed that although the workers received a high level of support from family and colleagues, they received relatively little support from society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our survey results also indicated a lack of appreciation by the affected communities regarding the work performed by the public health workers [ 33 ]. Our data showed that although the workers received a high level of support from family and colleagues, they received relatively little support from society.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that although the workers received a high level of support from family and colleagues, they received relatively little support from society. In contrast with the work of physicians and nurses, the work performed by public health workers is not widely understood and respected by the public [ 33 ]. During the epidemic, the types of prevention and control work performed by the public health workers, such as the isolation of close contacts (at home or designated hotels) and home inspections, were very likely to elicit negative emotions and even objections in communities.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported depression (21.3%) and anxiety (19.0%) among participants in our study were substantially higher than those of hospital medical staff in daily work in China (18.3% and 14.7%), using the same measurements and cut-off points. 34 Furthermore, in our study, a larger proportion of CDC workers reported mental health problems and poor physical health than PHI workers, as they might bear more responsibilities in regional disease prevention, 26 and had longer working hours. In studies targeting medical workers during SARS epidemic, 38.5% of hospital workers dealing with SARS patients developed symptomatic depression, 12 while in MERS-Cov epidemic, two thirds of medical workers reported psychological problems.…”
Section: Discussionmentioning
confidence: 54%
“…However, our survey also indicated a lack of appreciation of the communities toward the work performed by the public health workers [33]. Our data showed that support from family and colleagues is high, whereas the support from society is relatively low.…”
Section: Discussionmentioning
confidence: 57%
“…Our data showed that support from family and colleagues is high, whereas the support from society is relatively low. Compared with physicians and nurses, the work by the public health workers is not widely understood and respected by the public [33]. During the epidemic, prevention and control work that they were engaged in, such as the isolation of close contacts (at home or designated hotels) and home inspections, was very likely to cause negative emotions and even objection in the community.…”
Section: Discussionmentioning
confidence: 99%